Comparative Stress–Strain Study of Rubber and Metal: Implications for Cutting Resistance - Hagai, Rafael (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
This study aims to investigate the physical phenomenon that occurs when a sharp knife is inserted into rubber material under various strain conditions. The analysis is based on experimental data from